2001
DOI: 10.1046/j.1365-2141.2001.03021.x
|View full text |Cite
|
Sign up to set email alerts
|

Transient pancytopenia preceding acute lymphoblastic leukaemia (pre‐ALL) precipitated by parvovirus B19

Abstract: Summary. A preleukaemic phase, typified by pancytopenia and bone marrow (BM) hypoplasia, is an uncommon but well-documented prelude to acute lymphoblastic leukaemia (pre-ALL) in children. Parvovirus B19 (B19) exhibits a marked tropism to human BM and replicates only in erythroid progenitor cells acting as a confounding, but treatable agent in immunocompromised patients. We present the first case of B19-associated pre-ALL characterized by severe and recurring transient pancytopenia in a child who developed ALL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 19 publications
1
30
0
1
Order By: Relevance
“…However, several reports describe B19 infection preceding and mimicking ALL. [1][2][3][4] One published study examined serum from 65 patients with ALL for B19 DNA and specific IgG. 5 The results showed that although there was one positive case, which was also published separately, 1 serum anti-B19 IgG was positive in 30% of patients, which is consistent with the population prevalence adjusted for age.…”
mentioning
confidence: 62%
“…However, several reports describe B19 infection preceding and mimicking ALL. [1][2][3][4] One published study examined serum from 65 patients with ALL for B19 DNA and specific IgG. 5 The results showed that although there was one positive case, which was also published separately, 1 serum anti-B19 IgG was positive in 30% of patients, which is consistent with the population prevalence adjusted for age.…”
mentioning
confidence: 62%
“…Certain studies have reported that parvovirus B19 infection is associated with the inhibited status of bone marrow in pre-ALL children (16), and that children infected by parvovirus B19 are more susceptible to severe anemia (17). However, there was no evidence of such viral infection in the present patient.…”
Section: Discussionmentioning
confidence: 99%
“…, 1992; Lee, Kim & Bang, 1994; Sitar et al. , 1999; Heegaard, Madsen & Schmiegelow, 2001; Kerr et al. , 2003; Savasan & Ozdemir, 2003; Yetgin et al.…”
Section: Introductionmentioning
confidence: 99%